2023
DOI: 10.30935/cedtech/12659
|View full text |Cite
|
Sign up to set email alerts
|

Influences of subjective norms on teachers’ intention to use social media in working

Abstract: This study investigates factors affecting teachers’ intention to use the Zalo app–a social media with impressive users in Vietnam in recent years. The extended technology acceptance model (TAM) involves subjective norms (SNs) (colleagues, managers, students, and parents) and anxiety as the precursors of user attitude and intention to use as well as perceived ease of use (PEOU) and perceived usefulness (PU) as the key variables in TAM was employed. 1,105 teachers in Vietnam took part in the online survey. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…Contemporary Educational Technology, 15(1), ep404 transparent social media use, among others. The Call for Papers drew 13 articles, out of them five papers were accepted after peer review and recently published in this Special Issue (Castañeda & Villar-Onrubia, 2023;Montiel-Ruiz et al, 2023;Stewart, 2023;Torres-Hernández & Gallego-Arrufat, 2023;Tran et al, 2023). These five papers consist of two empirical studies and three case studies as practical experiences that connect to the proposed topic.…”
Section: /mentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary Educational Technology, 15(1), ep404 transparent social media use, among others. The Call for Papers drew 13 articles, out of them five papers were accepted after peer review and recently published in this Special Issue (Castañeda & Villar-Onrubia, 2023;Montiel-Ruiz et al, 2023;Stewart, 2023;Torres-Hernández & Gallego-Arrufat, 2023;Tran et al, 2023). These five papers consist of two empirical studies and three case studies as practical experiences that connect to the proposed topic.…”
Section: /mentioning
confidence: 99%
“…The two empirical studies of this Special Issue (Torres-Hernández & Gallego-Arrufat, 2023;Tran et al, 2023) are about very different themes and contexts which help address the implications of overcoming naive practices in social media.…”
Section: /mentioning
confidence: 99%
“…It is believed that subjective norms play a significant role in forming attitudes towards technology usage (Ursavaş et al, 2019 ). In Tran et al, ( 2023 ) study, subjective norm is regarded as an important variable. The results of their study confirmed the positive impact of digital usage on subjective norm, which can be also observed in other past studies, which have demonstrated strong positive interaction between subjective norm and digital usage (Binyamin et al, 2018 ; Zhuang et al, 2021 ).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Although a considerable amount of research has discussed that subjective norms are regard as the principal factor determining people's intentions against the backdrop of marketing and consumer behavior, including their vaccination intentions during the spread of Covid-19 (Kevin Winter et al,2021) [16] , social media-use intentions for Vietnamese teachers during working (Huong Thi Thu Tran et al,2023) [17] , entrepreneurial intentions for Indonesian students (Elissa Dwi Lestari et al,2023) [18] , and consumers' intentions to purchase safely certified vegetables in the emerging market (Hai Minh Ngo et al, 2023) [19] . Interestingly, as concluded by (Song-Lin Wong et al, 2018) [20] , subjective norms have no direct and significant effect on consumers' purchase intention to suboptimal foods.…”
Section: The Impact Of Subjective Norms On Impulsive Purchasing Behaviormentioning
confidence: 99%